THE EFFECT OF PROFITABILITY, LIQUIDITY, COMPANY SIZE, AND INVESTMENT DECISION ON COMPANY VALUE (A STUDY ON FOOD AND BEVERAGE SUB-SECTOR COMPANIES LISTED ON THE INDONESIAN STOCK EXCHANGE IN THE PERIOD 2019-2021) - Kristanti, Farida Titik; Emru, Radhitya Friyatama (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2024)
this study intends to ascertain the impact of profitability, liquidity, company size, and investment decisions on firm value. Eviews 12 software is used in this quantitative study, which employs the panel data regression method. in food and beverage sub-sector companies listed on the Indonesia Stock Exchange in the 2019-2021 period.  A total of 39 observations were acquired from the study's overall sample, which consisted of 13 companies during the course of the three time periods. The study's findings, company size, liquidity, and profitability have no effect on the company value of the food and beverage sub-sector listed on the Indonesia Stock Exchange in 2019–2021, while investment decisions have a significant positive impact on the company value of the listed food and beverage sub-sector companies on the Indonesia Stock Exchange in 2019–2021.